Síndrome de Burnout académico en estudiantes de secundaria durante la COVID-19: Lambayeque-Perú: Academic Burnout in secondary students during COVID-19: Lambayeque-Perú (Revista Médica de Trujillo, 2023)
Objetive: to determine the levels of the Academic Burnout Syndrome (SBA) and its dimensions, in 150 high school students from five state schools in the department of Lambayeque on the coast of Peru. Methods: the methodology used was of an applicative and descriptive level, the results were measured during the Pandemic generated by COVID-19 in the year 2020, between the months of April and June. Data collection was performed with informed consent and using a virtual questionnaire, using the Maslach Burnout Inventory Student Survey Questionnaire (MBI-SS) as a measurement instrument. Results: were analyzed with the statistical program IBM SPSS version 26, finding a High reliability level (Crombach's Alpha of 0.87). Conclusion: The results indicated that there is 9% of students with a High level of the SBA, 85% with an average level and 7% with a Low level. In relation to the dimensions of the SBA (Emotional Exhaustion, Cynicism and Academic Self-Efficacy), it was found that 15.3% of students presented a High level in High Emotional Exhaustion, 64.7% presented a Medium level and 20% a Low level. . In relation to Cynicism, 18% of students presented a high level, 49.3% a Medium level and 32.7% a Low level. On the other hand, 26.2% of students presented a High level in Academic Self-efficacy, 47.7% presented a Medium level and 26.2% a Low level.
Keywords: Academic Burnout Syndrome; emotional exhaustion; cynicism; academic stress; COVID-19